Perineal Laceration and Episiotomy Repair Using a Beef Tongue Model - Michelle Eston; Alyssa Stephenson-Famy; Hannah McKenna; Michael Fialkow (Association of American Medical Colleges, 2020)
Introduction Declining rates of operative vaginal deliveries and routine episiotomy in obstetric practice, along with rising cesarean section rates, have decreased OB/GYN resident experience with episiotomy repair and obstetric anal sphincter injuries (OASIS). Simulation models are valuable educational tools in procedural training. Several models have been reported, each with its own limitations and benefits. Methods We developed a 1-hour workshop to teach novice OB/GYN residents perineal laceration repair skills on a modified beef tongue model. The model required 5-10 minutes to assemble following written and video instruction, and learners had 30-50 minutes to practice using learner instructions. Learners were evaluated using a procedure checklist and global objective structured assessment of technical skills. To evaluate the session, we surveyed current faculty and residents, as well as residency graduates. Results Between 2008 and 2017, an estimated 82 OB/GYN residents participated in this activity, and 95 participants and facilitators received the survey. Forty-one (59%) respondents agreed that this model was similar to repairing OASIS in clinical practice. Our trainees reported that the optimal time for simulated OASIS repair was the R2 and R3 years; however, 90% of respondents felt residents should be offered this simulation yearly. Discussion Based on our survey of trainees, graduates, and faculty, we created a realistic simulated OASIS repair training, despite the limitation that the model lacked a rectum. Learners reported an interest in repeating the simulation frequently during residency to augment their clinical experience and increase perceived competence in third- and fourth-degree laceration repair by their graduation.